Analisis Penanganan Longsoran dengan Bronjong - Anderson, Ganda; Saggaf, Anis; Dewi, Ratna (Universitas Muhammadiyah Palembang, 2025)
In this study will discuss the analysis of avalanche handling in the area of river bends with gabions, Application of avalanche handling with gabions, rock material around the location will be utilized to the maximum, Because the location of the landslide is in lahat Regency near the border of Pagaralam City, In analyzing the gabion against the rolling moment and shear force, it will get a recommendation for the optimal dimensions of the gabion to increase soil stability, These results will later become a reference for planning avalanche handling in areas that have abundant sources of rock material.